Problem-Based Learning E-Module Using HTML 5 Package Platform to Improve Critical Thinking and Collaboration Skills in Biology Lessons - Yuniarti; Astija; Mursito S Bialangi; Mohammad Jamhari; Vanny M. Tiwow (LPPM Undiksha, 2025)
Advances in information and communication technology have brought changes in the education world, including using e-learning modules as a substitute for printed modules. However, students' lack of prior knowledge hinders participation in discussions and problem-solving. This study aims to create a problem-based e-learning module using the HTML5 Package (H5P) platform to improve student's critical thinking and collaboration skills in Biology subjects in Senior High Schools (SMA). This type of research is Research and Development (R&D) using the 4D model. The subjects of this study were 30 grade X students. The instruments used were validation sheets, essay questions, and observation sheets. Data analysis techniques used quantitative and qualitative analysis. The validation results showed that the developed e-learning module met the feasible category with a validity level of 73.46%, practicality by teachers of 88.57% (very practical), practicality by students of 82.7% (very practical), and its effectiveness reached the high category (N-gain 0.80). The implementation of this e-module showed an increase in students' critical thinking skills by 81.64% and collaboration skills by 91.31%, which are included in the very effective category. The results of this study prove that interactive learning using H5P can improve the effectiveness of learning and students' critical thinking and collaboration skills in the 21st century. This study implies that problem-based teaching e-modules using the HTML5 Package Platform in Biology subjects can improve students' critical thinking and collaboration skills.